Analisis Kebutuhan Bahan Ajar Buku Menulis Karya Ilmiah Mahasiswa STKIP PGRI Bandar Lampung - Tri Riya Anggraini; Fransisca S.O. Dedi; Awalludin Awalludin; Fadila Natasya (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2023)
The lack of references according to student needs is a problem in this research. For this reason, this research aims to analyze the need for developing teaching materials for writing scientific papers. The method used is descriptive and qualitative with research subjects being students of STKIP PGRI Bandar Lampung Semester III and V. The data collection tools used are interview guidelines and questionnaires. Data analysis uses Miles & Huberman data analysis with data reduction, data presentation and data validation. The research results require teaching materials, namely books according to the learning objectives. It is hoped that this research can become a reference in creating or developing teaching materials in the form of books as a learning medium for writing scientific papers.